Community Rules: Utilizing Customary Law to Combat Environmental Degradation in the South Pacific - Marissa Cripe (Washington University Global Studies Law Review, 2025)
The South Pacific is home to some of the most biodiverse ecosystems in the world. This rich biodiversity is important to South Pacific island nations for economic and cultural reasons. Yet, the region is highly vulnerable to ecosystem changes. Therefore, South Pacific island nations are expected to be some of the first to feel the effects of climate change, despite contributing little to global climate pollution. The South Pacific and its nations also face other man-made threats to its environment, such as: unsustainable logging, particularly in the Solomon Islands; overfishing and other harmful fishing practices (such as the use of dynamite on coastal reefs), which, in combination with pollution, has led to a significant decline in fish stock; and the unsustainable use of land. These types of unsustainable land uses have many impacts, including soil erosion, sedimentation on coral reefs affecting the growth of coral, and the degradation of mangroves due to their misuse as wastelands. Is there a solution to the mounting environmental problems South Pacific Island nations face? One possible solution is greater adoption and use of customary law and traditional knowledge to address environmental issues that fall within their control. There are South Pacific island nations currently using customary law and traditional knowledge for resource management for resource management, regulating practices such as hunting, land use, forest management, and fishing and marine harvesting. This paper looks at the current adoption and use of some of these laws while exploring the possibility of using customary law and traditional knowledge to combat the wider range of environmental crises threatening South Pacific Island nations. Section I will define customary law and explore its current use by South Pacific Island nations. Section II will examine the particular case of Samoa’s use of customary law to help combat the environmental problem of overfishing and marine degradation and explore whether it can be transposed to other South Pacific Island nations. Section III will look to the case studies of Papua New Guinea’s (“PNG”) and the Solomon Islands’ attempts to use customary law to address their countries’ environmental concerns. Finally, Section IV will explore possible explanations for why customary law has worked for some South Pacific island nations and not for others, examining factors such as population size, lack of respect for customs and customary law, lack of accountability once rules and laws are enacted, and economic dependence on natural resources to determine whether the adoption and use of customary law to combat environmental harms is successful. This paper suggests that for environmental and conservation laws to work they must be community-based. This is where customary law plays a crucial role—the local community understands its needs and the resources it must protect better than the outside government, and can therefore better respond to those needs and problems themselves.
Keywords: Customary law; environmental degradation; environment; environmental; south pacific; biodiversity; biodiverse ecosystem; environmental changes; ecosystem changes; climate change; climate pollution; unsustainable logging; Solomon Islands; overfishing; fishing; unsustainable; sustainable; soil erosion; sedimentation; coral reefs; mangroves; wastelands; resource management; hunting; landuse; forest management; marine harvesting; papua new guinea; conservation laws